KEPEMIMPINAN PERSPEKTIF ALQURAN; INTERPRETASI SEMIOTIK QS. AL-BAQARAH (2): 30-34 - Andi, Azhari (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2019)
Discourse of leadership is always facual and actual to be discussed. It is increasingly discussed by Indonesian in which general elction is coming up this year. This article attempts to examine discourse of leadership on QS. Al-Baqarah 2 / 30-34 which is analyzed through semiotic perspective that is introduced by Charles Sander Pierce. The article finds that requirement of being khalifah which is discussed by Q. 2/31-34 is having knowledge. Besides, spiritual piety is needed to become khalifah but not as significant as having knowladge.  In the other hand, the Qur'an, by Q. 2/31-34, criticizes that to become a leader is not depending on lineage factors and spiritual piety (only).